Advances in Application of Fuzzy sets in electrical engineering - Aditya Jain; Balakrushna Tripathy (Institute of Advanced Engineering and Science, 2017)
Initially a theory, today fuzzy logic has become an operational technique. Used alongside other advanced control techniques, it is making a discrete but appreciated appearance in various electric systems. In the majority of present-day applications, fuzzy logic allows many kinds of designer and operator qualitative knowledge in electrical automation to be taken into account. Fuzzy logic began to interest the media at the beginning of the nineties. The numerous applications in electrical and electronic household appliances, particularly in Japan, were mainly responsible for such interest. Washing machines not requiring adjustment, camcorders with Steadyshot (TM) image stabilization and many other innovations brought the term “fuzzy logic” to the attention of a wide public.